Mutational and epigenetic signatures in cancer tissue linked to environmental exposures and lifestyle. Issue 1 (January 2018) - Perduca, Vittorio; Omichessan, Hanane; Baglietto, Laura; Severi, Gianluca
Abstract : Purpose of review: In this article, we describe how recent advances in the study of mutational and epigenetic signatures in tumours provide new opportunities to understand the role of the environment and lifestyle in cancer development. Recent findings: Cancer-related mutational events have been investigated for decades but only recently the wide availability of genomic sequences and epigenomic data from thousands of cancer genomes has made it possible to identify numerous distinct mutational and epigenetic signatures through the application of advanced mathematical models. Some of these signatures have been linked to endogenous factors such as defective DNA repair or the action of APOBEC cytidine deaminases and to exogenous factors such as tobacco smoke, ultraviolet light, aflatoxins, aristolochic acid and ionizing radiation. More recently, it has been shown that exposure to factors such as tobacco smoke may also leave marks in the DNA methylation profile of both normal and tumour tissue in target organs. Summary: The analysis of mutational and epigenetic signatures is a novel and useful tool to study cancer. Their application to experimental studies and to studies with detailed data on environmental exposures and lifestyle is likely to improve our understanding of how the environment and lifestyle influence cancer development and its evolution.